A Brief Analysis of IUCN Red Listed Threatened Plants of India - Kumar, Puneet; Panwar, Giriraj Singh; Singh, S. K. (Indian Forester, 2022)
The newest assessment of Indian plant richness stands at 54733 taxa which include 21849 angiosperms, 15504 fungi, 8979 algae, 2791 bryophytes, 2961 lichens, 1257 microbes, 1310 pteridophytes and 82 gymnosperms. Of these, the IUCN Red List for Indian plants includes 416 angiosperms, 12 gymnosperms, 2 pteridophytes, 7 bryophytes and 1 fungal species under various threat categories. In current communication, the authors discuss various IUCN threat categories and analyse in brief the Red listed threatened plants of India.